2007
DOI: 10.1186/1751-0147-49-22
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study on the occurrence of Cryptosporidium and Giardia in dogs during their first year of life

Abstract: Background: The primary aim of this study was to obtain more knowledge about the occurrence of Cryptosporidium and Giardia in young dogs in Norway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
3
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 44 publications
7
28
3
8
Order By: Relevance
“…The overall prevalence of 20.5% Giardia infection identified in this study is similar to that previously reported in Denmark (17.1%) (Hansen et al, 2000), the former Yugoslavia (14.4%) (Nikolic et al, 2002), Norway (20.7%) (Hamnes et al, 2007) and Italy (15-32.1%) (Giangaspero et al, 2002;Capelli et al, 2003;Berrilli et al, 2004;Bianciardi et al, 2004;Capelli et al, 2006). Although Papini et al (2005) and Szénàsi et al (2007) found high prevalences of infection of 55.2% and 58.8% in kennelled dogs using a G. duodenalis-specific coproantigen ELISA, the discrepancy found by Szénàsi et al (2007) between prevalence as determined by this method and by microscopy (7.5%) suggests some caution should be applied in use of this diagnostic method (Cirak and Bauer, 2004;Mekaru et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…The overall prevalence of 20.5% Giardia infection identified in this study is similar to that previously reported in Denmark (17.1%) (Hansen et al, 2000), the former Yugoslavia (14.4%) (Nikolic et al, 2002), Norway (20.7%) (Hamnes et al, 2007) and Italy (15-32.1%) (Giangaspero et al, 2002;Capelli et al, 2003;Berrilli et al, 2004;Bianciardi et al, 2004;Capelli et al, 2006). Although Papini et al (2005) and Szénàsi et al (2007) found high prevalences of infection of 55.2% and 58.8% in kennelled dogs using a G. duodenalis-specific coproantigen ELISA, the discrepancy found by Szénàsi et al (2007) between prevalence as determined by this method and by microscopy (7.5%) suggests some caution should be applied in use of this diagnostic method (Cirak and Bauer, 2004;Mekaru et al, 2007).…”
Section: Discussionsupporting
confidence: 91%
“…Despite the results of the current study, in some researches the frequency of Cryptosporidium infection was higher in young dogs (21,31,33,46). Some studies in comparison to the current study indicated that infection rates in female dogs were higher than male dogs, which may be due to reduced immunity at certain periods in female physiologic cycle (32).…”
Section: Discussioncontrasting
confidence: 83%
“…Istedenfor å presentere disse funnene har Landvik konsentrert seg om en undersøkelse av unge hunder (5). Selv om den kumulative prevalensen fra denne studien, slik de er sitert, var relativt høy (44 % for Cryptosporidium og 21 % for Giardia), så var den individuelle prevalensen bare halvparten hos valpene (23 % for Cryptosporidium og 12 % for Giardia) og langt lavere hos tispene (< 3 % for Giardia og < 4 % for Cryptosporidium).…”
Section: Er Smitte Fra Hund Sannsynlig?unclassified